Comparation of Sexual Violence Crimes Based on Law Number 12 of 2022 by Law Number 1 Of 2023" - Melkianus Radja, Frengki; Winjaya Laksana, Andri (Jurnal Hukum Khaira Ummah, 2025)
Sexual violence crimes constitute a violation of human rights that require comprehensive legal protection. In Indonesia, the regulation regarding sexual violence has undergone significant development with the enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes (UU TPKS) and the promulgation of Law Number 1 of 2023 on the Criminal Code (KUHP 2023). These two laws serve as the legal basis for addressing sexual violence, each having different approaches, scopes, and substantive provisions. This study aims to analyze and compare the regulation of sexual violence crimes between the TPKS Law and the 2023 Criminal Code, focusing on the elements of the offense, recognized forms of sexual violence, and towards approaches to victims. The research employs a normative juridical method with a statutory and conceptual approach. Data were collected through literature review and analyzed qualitatively. The results indicate that the TPKS Law functions as a lex specialis, providing broader protection and being more victim-centered, covering a wider variety of sexual violence forms. Meanwhile, the 2023 Criminal Code regulates sexual violence within a more limited scope but incorporates several provisions from the TPKS Law as part of national criminal law harmonization. Although there are some overlapping norms, both laws can complement each other if implemented properly. This study recommends the importance of synchronization and harmonization between the TPKS Law and the 2023 Criminal Code to optimize legal protection for sexual violence victims within Indonesia's criminal justice system.